KARAKTERISTIK DAUN DAN RENDEMEN MINYAK ATSIRI LIMA JENIS TUMBUHAN KAYU PUTIH - Ary Widiyanto; Mohamad Siarudin (BRIN Publishing, 2013)
Leavessignifies as the most important part of cajuput-oil-producing tree species from which the corresponding oil is extracted. Dimensionof leaf vary among different genus and even among different trees within the same genus as well as within the same species. In relevant, this research aimed to look into the characteristics of the leaf and essential oil yield of the five cajuput-oil-producing tree species. Those investigated species consisted of Melaleuca viridiflora (red-flowered trees), M. vindiflora (wbite-flowered trees), M. cajuputi. Asteromyrtus brasii and A. symphiocarpa, which altogether indigenously grew at Wasur National Park, in Meranke (Papua). From those five species, approximately 6 kg of fresh leaf was taken and prepared for the steam-distillation process to extract their cajuput oil. In total, there were about 120 pieces of leaves as sampled that represented the dimension of all those five species. Results shows that the leaves of M. viridiflora cochibited the biggest dimension (length and width), while those of consecutively M. caiuputi bus the smallest length and A. brasii, bad the smallest width. Letter of A. symphiocarpa afforded the biggest sil yield (1,43%) and Melaleuca viridiflora (red-flowered trees) bad the smallest oil yield (0,1%).